The relationship between addiction and depression, spouse abuse, and addicts' personality types - Sadeghzadeh, Marziyeh; Sedaghat, Mastoreh (Journal of Assessment and Research in Applied Counseling (JARAC), 2020)
Aim: This study aimed to determine the relationship between addiction and depression, spousal abuse, and personality types in addicts in the Sixty Congress of 4 Faith. Method: This study was conducted in the form of a descriptive correlational study. The statistical population of the present study consisted of all addicted people in the Sixtieth Congress in Tehran (Region 4) Iman Branch in 2016; From 182 addicts according to the Morgan table, a sample of 120 people was randomly selected and the data were performed based on questionnaires of depression, attitudes toward addiction, spouse abuse, and personality types. To analyze the data from the matrix of correlation coefficient and multiple regression used. Results: The results showed that there was a significant positive relationship between addiction with depression and spousal abuse in addicts and a significant negative relationship with extroverted personality type, but no relationship was found between addiction and introverted personality type. There was also a negative relationship between spouse abuse and depression and a negative relationship between introverted and extroverted personality types with depression and a positive positive relationship between extroverted personality types with spouse abuse. Conclusion: According to the results of this study, it can be concluded that addiction can increase the rate of depression and spousal abuse, as well as personality types that can affect addiction, depression, and spousal abuse.